Diversity and abundance of insects at industrial plantation forest and natural forest ecosystems in Siak, Riau Province - Asril Asril; Yossa Istiadi; Budi Tjahyono (Universitas Pakuan, 2020)
The objective of research is to find out the differences and similarities of insect diversity, abundance and composition between in industrial plantation forest (HTI) and natural forest (Arboretum) ecosystems. Field research was carried out in the Rasau Kuning area, Perawang Barat Regency, Riau Province, while specimens identification conducted at LIPI Biology Research Center Laboratory in February - March 2019. Line transect sampling technique and fluorescent light traps were used as methods for collecting insects from both two different ecosystems with three replications. The results found five order of insects i.e. Lepidoptera, Hemiptera, Coleoptera, Orthoptera, and Hymenoptera which consisting of 35 species in plantation forest ecosystem, and 26 species in natural forest ecosystem where both ecosystems dominated by Lepidoptera. Statistical analysis of research results show that two average insects species diversity index within both plantation forest (HTI) and natural forest (Arboretum) ecosystems is not different (t = 1,419; p0,05). The similarity index found very similar (23,56%) between both ecosystems. Predatory insects which was found in this study is Sycanus sp. (Hemiptera: Reduviidae) from the order of Lepidoptera.Penelitian ini bertujuan untuk mengungkapkan perbedaan dan kesamaan keanekaragaman jenis, kelimpahan, dan komposisi jenis serangga antara di ekosistem hutan tanaman industry (HTI) dengan ekosistem hutan alam (Arboretum). Penelitian lapang dilakukan di areal Rasau Kuning, Kabupaten Perawang Barat, Provinsi Riau, sementara identifikasi specimen dilakukan di Laboratorium Pusat Penelitian Biologi LIPI, pada bulan Pebruari - Maret 2019. Metode sampling line transect dan perangkap cahaya berflouresen digunakan untuk menangkap serangga di kedua ekosistem tersebut melalui 3 kali ulangan. Hasil studi menemukan 5 ordo serangga yaitu Lepidoptera, Hemiptera, Coleoptera, Orthoptera, and Hymenoptera, dengan masing-masing 25 spesies terdapat di ekosistem hutan tanaman (HTI) dan 26 spesies di ekostem alam (Arboretum), yang mana keduanya didominasi ordo Lepidoptera. Melalui analisis statistik, hasil penelitian menunjukkan bahwa pada kedua ekosistem tidak terlihat adanya perbedaan indeks keanekaragaman jenis (t =1,419; p0,05). Begitu juga dengan indeks kesamaan menunjukan tingkat yang sangat sama (23,56%) antara kedua ekosistem tersebut. Pada kajian ini juga ditemukan spesies serangga predator yaitu Sycanus sp. ((Hemiptera; Reduviidae) dari ordo Lepidoptera.